A uniqueness test regarding the sequence of multipliers generated by the Augmented Lagrangian Method - Rezza Espinoza, Yna Consuelo (2018)
This paper presents a proof of the unicity of the sequence of multipliers generated by the Aumented Lagrangean Method with Penalties P, EP. This unicity has beentested along the last 25 years by the use of the equivalence relationship existing between the Aumented Lagrangean and Proximal Point Methods Various researchers such asRockafellar [10]. Iusem [6] and Gonzaga & Castillo [2] tested this equivalence and the consequent unicity of the multipliers sequence generated by the AumentedLagrangean Method in particular cases. The proof we are presenting includes all these cases; it is outstanding for being direct and not to use the above equivalence relation.